Self-regulation of pharmaceutical activity in Ukraine: opinion of pharmacists and pharmacy technicians - B. Р. Hromovyk; O. B. Pankevych; G. I. Bilushchak (The State Expert Center of the Ministry of Health of Ukraine, 2020)
The Sustainable Development Goals for 2016-2030, approved in September 2015 at the United Nations Summit, are possible only if the institution of self-regulation of pharmaceutical activities (SRFD) is built and further effective cooperation of public authorities with self-regulatory pharmaceutical organizations (SRPhO). The results of the study of sources of scientific literature show that various aspects of the formation of SRPhA in Ukraine have been studied by a number of domestic researchers. Despite this, a number of little-studied and debatable issues remain that require further research. The aim of the work was to study the opinion of pharmacists and pharmacy technicians on the understanding of the essence and necessity of introducting SRPhA in Ukraine, their readiness to become members of SRPhO. To reach this goal, the following methods were used: questionnaires, mathematical statistics, generalization and interpretation of results. The primary data were taken from 894 questionnaires, 827 of qualitatively completed face-to-face and part-time questionnaires were selected and processed, they were conducted in the majority (16 out of 25) of regions controlled by the Government of Ukraine. According to the results of a questionnaire survey of pharmaceutical specialists (PhS), including 67.1% of pharmacists and 32.9% of pharmacy technicians, the respondents' level of acquaintance with the basic principles of self-regulation of certain markets is extremely low: 17.7% among pharmacists and 15.1% among pharmacy technicians. Nevertheless, 38.2% of the surveyed pharmacists and 36.8% of other respondents have a positive attitude to the possibility of SRPhA, the principle of obligation of which for all market participants was fully supported by 14.0% of pharmacists and 16.2% of pharmacy technicians. Instead, almost two-thirds of respondents (64.5% and 62.9% of the relevant groups) believe that only pharmaceutical specialists can be members of the SRPhO, and 25.4% of pharmacists and 21.3% of pharmacy technicians are willing to become its members voluntarily. Thus, found the similarities of both groups of PhS regarding their familiarity with the basic principles of self-regulation of individual markets, their attitude to the possibility and binding nature of SRPhA, membership in the SRPhO and attitude to this membership. At the same time, the survey showed their insufficient understanding of the essence and necessity of SRPhA implementation. Given the development of SRPhA in well-developed countries and it's nurturing at the legislative level of Ukraine, there is a need to promote the idea of SRPhA among PhS and contact audiences, which are endowed with control functions, and those who do not have such functions.